2015
DOI: 10.1016/j.pbb.2014.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Proficient motor impulse control in Parkinson disease patients with impulsive and compulsive behaviors

Abstract: Background Parkinson Disease (PD) patients treated with Dopamine Agonist therapy can develop maladaptive reward-driven behaviors, known as Impulse Control Disorder (ICD). In this study, we assessed if ICD patients have evidence of motor-impulsivity. Methods We used the stop-signal task in a cohort of patients with and without active symptoms of ICD to evaluate motor-impulsivity. Of those with PD, 12 were diagnosed with ICD symptoms (PD-ICD) and were assessed before clinical reduction of Dopamine Agonist medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 52 publications
(54 reference statements)
3
34
1
2
Order By: Relevance
“…However, when selective suppression became effective (second slope), there ceased to be a difference in suppression efficiency between the two groups. This lack of a significant difference in the second part of the distribution contrasts with previous studies showing that patients with PD have impaired impulse suppression even when they respond slowly enough to allow the suppression process to get going [30,31,[37][38][39][40][41]. This difference can be explained by the fact that we estimated the temporal dynamics of the responses with only three bins, compared with between five and seven bins in the above-cited studies, leading to a less accurate representation of response distribution.…”
Section: Discussioncontrasting
confidence: 79%
“…However, when selective suppression became effective (second slope), there ceased to be a difference in suppression efficiency between the two groups. This lack of a significant difference in the second part of the distribution contrasts with previous studies showing that patients with PD have impaired impulse suppression even when they respond slowly enough to allow the suppression process to get going [30,31,[37][38][39][40][41]. This difference can be explained by the fact that we estimated the temporal dynamics of the responses with only three bins, compared with between five and seven bins in the above-cited studies, leading to a less accurate representation of response distribution.…”
Section: Discussioncontrasting
confidence: 79%
“…Pramipexole increased waiting impulsivity and impulsive action both in sham and lesioned rats but its effect on waiting impulsivity in lesioned rats was enhanced in animals with pre-existing impulsivity traits 105 . However, in contrast to impairments in decisional impulsivity in humans, studies either did not detect impairments 93 or showed improvement 106 in motor response inhibition in PD+ICD subjects tested using the stop signal task. Contrasting with ICDs, PD patients with LID display altered motor inhibition, as shown with decreased reaction time during erroneous stop trials 107 .…”
Section: Risk and Uncertaintymentioning
confidence: 76%
“…Finally, a single study reported better executive functions in ICD+ ( 24 ). Reports on affective factors are also inconclusive, as self-reported depression and anxiety were sometimes found to be associated with ICD ( 18 , 20 , 21 , 25 28 ), and sometimes not ( 3 6 , 17 , 19 , 22 , 29 31 ). However, motivational factors such as self-reported apathy ( 11 , 21 , 27 , 28 ), anhedonia ( 27 , 32 ), and impulsivity ( 17 , 20 22 , 32 ) appeared to be elevated in ICD+ vs. ICD–.…”
Section: Introductionmentioning
confidence: 99%